MUHAMMAD SYAHRUR DAN TEORI LIMITASI: Sebuah Metode Penggalian Hukum Islam - Witro, Doli (Istinbath : Jurnal Hukum, 2021)
One of the thinkers in Islam who has contributed to the contemporary era is Muhammad Syahrur. It offers a contemporary methodology in explaining Islamic law. He further stated that in understanding the texts, one should not always be fixated on the interpretation of traditional ulama because religious texts should be interpreted according to their era. In explaining the renewal of Islamic law, Syahrul introduced a theory called the limit theory. This paper discusses the limit theory, which Muhammad Syahrur popularized. This paper aims to explain ijtihad in other languages ​​extracting Islamic law using the limit theory introduced by Syahrur. This article uses a library research method. The data in this article were analyzed qualitatively, namely data reduction, data presentation, and conclusion drawing. The analysis results show that the hudud theory or limit theory as a tool for criticism of the established methodology of Islamic law (ushul fiqh) is a good thing. However, to rely on the hudud theory or limit theory as the main method in extracting Islamic law as a substitute for the ushul fiqh method that mujtahids have used in extracting Islamic law, the hudud theory or limit theory is still not well established.